Comparison of the existing and calculated blast design parameters for the rock mass conditions at Bamesso-Latet rock quarry - Ousmanou, Safianou; Blaise, Ndapeh Nd.; Martial, Fozing Eric (Journal of Nepal Geological Society, 2020)
Blasting is the most cost effective methodology to break rock for mining engineering applications. A good production blast will break only the rock that is needed to be removed, leaving the host rock with minimal damage. Accurate measurement of blast, fragmentation is important in mining and quarrying operations, in monitoring and optimizing their design. Currently, there are several methods available to predict damage due to blasting. The accuracy of many of these methods is questionable, and in most cases, the methodologies over predict the results. This paper presents a practical method (i.e. Langefors’s method) that we shall use in Bamesso-Latet rock quarry to do a comparison between the existing and calculated blast design parameters. The proposed method allows to assess the rock damage from blasting. It shows great potential as a practical aid to control and get a good quality of the fragmented material in Bamesso-Latet rock quarry.